"Happy consciousness": Hegemony and hidden curricula in literacy readers between 1977 and 1991 - Allan B. Quiglye; Ella Holsinger (Adult Education Research Conference, 1993)
When five widely used literacy series were content analyzed in 1977, racism, sexism and socio-economic stereotyping were discovered to "abound" in the texts. This reconstruction of that study finds today's readers have improved, but only slightly.